Structural basis of host protein hijacking in human T-cell leukemia virus integration - Veer Bhatt (Nature Portfolio, 2020)
Integration of the reverse-transcribed viral DNA into host chromosomes is a critical step in the life-cycle of retroviruses such as the human T-cell leukemia virus type-1 (HTLV-1). Here the authors describe the structural role of the host co-factor protein phosphatase 2A B56γ subunit in supporting integration as part of the HTLV-1 intasome.